STUDY OF THE COMPOSITION OF PISCO OF DIFFERENT VARIETY OF GRAPES FROM PISCO FROM THE MUST TO THE PRODUCT (PART I - THE MUST) - Linares F., Thais (2008)
It reproduces the process of preparing the pisco since the preparation of the grape juice to final product for seven of the eight varieties of grapes for Pisco. In this first part is reported the composition of the musts obtained and the fermented grape. The analysis is done by gas chromatography.